PENGARUH PENGGUNAAN MEDIA SOSIAL TWITTER TERHADAP PARTISIPASI POLITIK ONLINE MAHASISWA DI JAWA BARAT - Hady Surya, Muhamad Satria; Pratamawaty, Benazir Bona (Fakultas Politik Pemerintahan, 2022)
According to several studies, there is an influence of the use of social media on a person's political participation. Therefore, this study aims to determine more specifically the influence of the use of social media Twitter on the online political participation of students in West Java. The method used in this research is descriptive quantitative. In this study, researchers describe whether the use of social media Twitter can affect or not affect the political participation of students in West Java. The population used in this research is active students who are in West Java. The sampling technique used is convenience sampling. This study used a Likert scale questionnaire (5-points) distributed via social media as a data collection technique to collect primary data. From the results of data analysis, the results show that there is an influence of the use of social media Twitter on the online political participation of students in West Java.